Rekonstruksi Butir Soal dalam Penilaian Keterampilan pada KD 3.7 dan KD 4.7 Teks Hikayat - Zuhra Sl. Datu; Wagiran Wagiran; Deby Luriawati Naryatmojo (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
One of the literary expressions taught in the Education Unit Level Curriculum in Senior High Schools is Hikayat Text. Saga Text Learning is one of the basic competencies that is integrated into the Indonesian language curriculum at Senior High Schools (SMK/SMA). Hikayat text is to express inner experiences about life through the medium of written language in which the words are coherent and intact. For students, Hikayat Text is not just a requirement to get grades from the teacher, but the process of expressing ideas in the form of words. Therefore, to achieve competence, students must be able to determine the values ??of the Hikayat Text. The purpose of the research is to reconstruct the items in the saga text KD 3.7 and 4.7 learning tools found in Taruna Bhakti Vocational School, Islamic Vocational School 1 Ambawa, and SMKN 1 Banggai. The research method used is descriptive qualitative. Qualitative data analysis includes content validity and constructs validity. The instrument used is the author acts as a data collector and data analyzer. Qualitative analysis instruments include content validity and construct validity analysis. A qualitative analysis of the items was conducted to determine the content validity and construct validity. In addition, qualitative analysis can be studied by covering the material domain, construction domain, and language domain. Reconstruction of questions is done by examining questions that are not in accordance with content validity or construct validity. The results of the analysis of the three RPP 3.7 and 4.7, namely RPP SMK Taruna Bhakti at KD 3.7 have 100% material aspects for construction aspects 96% cultural/language aspects 100% and analysis on RPP SMK Taruna Bhakti KD 4.7 there are material aspects 100% are appropriate, for Aspects construction 100% It is suitable for language/cultural aspects 100% is appropriate. RPP 2 SMK Islam Sudirman 1 Ambawa at KD 3.7 and KD 4.7 has 100% appropriate material aspects, 99% of construction aspects are not appropriate and 100% cultural/language aspects are appropriate. RPP 3 SMKN 1 Banggai at KD 3.7 and KD 4.7 has 100% appropriate material aspects, 97% of construction aspects are not appropriate and 100% of cultural/language aspects are appropriate.